INVENTARISASI DAN KARAKTERISASI JAMUR LIAR YANG DAPAT DI KONSUMSI DI DESA WONOJATI KECAMATAN GONDANGWETAN KABUPATEN PASURUAN - JAWA TIMUR - Khoirul Anwar; Rela Setyawati; Candra Krida Charisma (Universitas Sebelas Maret, 2014)
Abstract -Diversity of wild mushrooms in Indonesia is still not widely studied. Among the species of wild mushrooms can be consumed. Need to do an inventory and characterization of the various species of wild mushrooms, especially edible mushrooms. This study aims to inventory and characterize wild mushrooms that can be consumed by the Society in the Wonojati Village, Subdistrict of Gondangwetan, District of Pasuruan, East Java. The study was conducted in February-March 2014. Research method used is purposive sampling methods. Location of collecting mushrooms are grouped into 3 areas including paddy field, plantation areas and residential areas. Mushroom samples obtained from Wonojati village, Subdistrict of Gondangwetan, Pasuruan District. The results of the study were found 3 groups of wild mushrooms consumed by the society of Wonojati Village, namely Termitomyces, Auricularia, and Volvariella. Found 6 species of mushrooms belonging to the genus Termitomyces. Each mushroom has a different morphological characteristics that predicted different species but still into one genus. Termitomyces character is the growing medium in the form of termite nests that is below the ground surface. Another group of mushrooms are Auricularia and Volvariella. Auricularia has a character that resembles the shape of the ear. Volvariella has a volva characters. From some wild mushrooms were found to have been cultivated for consumption by the public is Auricularia and Volvariella. Termitomyces is still not cultivated mushrooms so there are opportunities to be cultivated as a food diversification efforts.Keywords : inventory, wild mushrooms, characterization